Detail of Frog - Adelaide de Menil (1967)
This is the view looking up at one of three frogs on the pole. The frogs represent three Kiksadi women, Tlingit whom belong to the frog clan. The three women cohabitated with Chief Shakes' slaves. The pole is said to be a ridicule pole carved to force payment for the Kiksadi Chief who would not pay for Shakes housing the three women. The Kiksadi Chief had said the women disgraced themselves, by marrying beneath them